Acute concussion: making the diagnosis and state of the art management. Issue 3 (June 2018) - Eisenberg, Matthew; Mannix, Rebekah
Abstract : Purpose of review: Concussion is an increasingly common injury in children. We aim to review the basic epidemiology and management of acute concussion and highlight recent studies that have contributed to our understanding of care for this injury. Recent findings: While concussion is considered a 'mild' form of traumatic brain injury, recent evidence suggests that as many as 30% of children are still symptomatic 1 month after injury. Although there is increasing interest in finding objective measures of injury and recovery, emerging imaging and serum biomarkers are not ready for routine clinical use. Identification of children at risk for prolonged symptoms is vital. Prolonged rest after injury may worsen outcomes. Summary: Concussion is a common injury in children. Objective measures of injury and recovery are needed, as are targeted therapies to mitigate the risk of prolonged recovery after injury.